Religious significance of suffering and psychological position in faith (Psicologia USP, 2004)
The psychological bond between the existencial experience of suffering and the position of the subject in relation to religious faith are studied. The investigation comprised 80 nurses, from both sexes, with various degrees of adherence to Christianism. The hypothesis was that these persons are impelled to structure for themselves a more or less stable, conscious or reflected attitude towards suffering. A questionnaire was elaborated including a question concerning suffering (dimensions, psychological aprehension, meaning), a question about the religious position (central or peripheric, certain or hesitant) and a question concerning the atribution of religious conotations to suffering. Results do not allow one to enunciate a homogeneous theory on the relation between religion and suffering, but the existence of singular configurations more or less stable and evolving, according to the religious attitude basic orientation, the merely human context of suffering and the religious contextualization of suffering.